The experience in parallelizm of a probability theory task - Krylovas, Aleksandras; Raulynaitis, Juozas (Lietuvos matematikos rinkinys, 2003)
The analysis of the parallel variants of a probability theory task are presented. The results of testing by Vilnius Gediminas Technical University second year students are proposed.